2020
DOI: 10.1038/s41598-020-70168-x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic radiogenomics in lung cancer: associations between FDG PET image features and oncogenic signaling pathway alterations

Abstract: this study investigated the associations between image features extracted from tumor 18 F-fluorodeoxyglucose (FDG) uptake and genetic alterations in patients with lung cancer. A total of 137 patients (age, 62.7 ± 10.2 years) who underwent FDG positron emission tomography/computed tomography (PET/CT) and targeted deep sequencing analysis for a tumor lesion, comprising 61 adenocarcinoma (ADC), 31 squamous cell carcinoma (SQCC), and 45 small cell lung cancer (SCLC) patients, were enrolled in this study. From the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…We also found that glycolytic entropy was significantly higher in patients with an advanced staging status, whereas genomic heterogeneity showed no significant difference. As tumor glycolysis is associated with oncogenic signaling pathway alterations [ 8 , 28 ], glycolytic features are associated with more aggressive behavior and metastatic potential [ 5 , 28 ]. Herein, the intensity, volumetric and heterogeneity glycolytic features were positively linked to higher cancer staging, suggesting that glycolysis is a biomarker of tumor aggressiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that glycolytic entropy was significantly higher in patients with an advanced staging status, whereas genomic heterogeneity showed no significant difference. As tumor glycolysis is associated with oncogenic signaling pathway alterations [ 8 , 28 ], glycolytic features are associated with more aggressive behavior and metastatic potential [ 5 , 28 ]. Herein, the intensity, volumetric and heterogeneity glycolytic features were positively linked to higher cancer staging, suggesting that glycolysis is a biomarker of tumor aggressiveness.…”
Section: Discussionmentioning
confidence: 99%
“…These features also reportedly predict pathological response after neoadjuvant chemoradiotherapy in patients with NSCLC [ 4 , 5 , 6 ]. The combination of gene tests and metabolic radiomics of 18 F-FDG PET (radiogenomics) has gained increasing attention in NSCLC research [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The literature on radiogenomics has greatly expanded in the past decade. Radiogenomics has been applied in various types of cancer, including lung cancer [70][71][72], breast cancer [73][74][75], genitourinary cancer [76][77][78], digestive system cancer [79][80][81], and brain cancer [82][83][84]. The comprehensive analysis method of radiogenomics can be used to diagnose and predict patient outcomes such as recurrence, metastasis, and survival of patients with cancer; predict the tumour microenvironment; identify potential molecular biomarkers and targets for clinical diagnosis and treatment; and establish a molecular typing system of variable cancers.…”
Section: Current Applications Of Radiogenomics In Cancermentioning
confidence: 99%
“…Considering this issue (Bai et al 2016, Bodalal et al 2019. For example, in a study by Kim et al (2020), FDG PET/CT imaging features were associated to genetic alterations in patients with lung cancer. In this study, association between PET features and alterations in oncogenic signaling pathways such as Cell cycle, WNT, p53 and TGFβ were determined and association between SUVpeak and SUVmax and mutation in TGFβ signaling pathway was found.…”
Section: Dl-based Featuresmentioning
confidence: 99%